All gain and no pain? Impacts of different green human resource management practices on employee green behavior: Evidence from Chinese electric vehicle sector - Xie, Huirong; Ho, Ree Chan; Ismail, Nurlida; Lau, Teck Chai (Journal of cleaner production, 2024)
Despite much research focusing on green human resource management, there is still a lack of comprehension regarding when and how different green human resource management practices influence employee green behavior. This research aims to construct and verify a research model in which different green human resource management practices influence employee green behavior through mediated pathways of perceived organizational green support and by interactive impact of employee green value. Structural equation modeling and importance-performance map analysis were performed based on survey data collected from 333 employees working in Chinese electric vehicle companies. The results revealed that most investigated practices are positively related to employee green behavior, and most of these relationships are mediated by perceived organizational green support and moderated by employee green value. However, green reward management negatively influences employee green behavior, and perceived green support does not mediate this relationship. Meanwhile, employee green value weakens green reward management’s negative impact on employee green behavior, while it does not moderate relationships between green training and development, nor green performance management and green behavior. Additionally, findings indicate that green training and development exhibits the highest performance while green involvement and engagement has the greatest total effect on employee green behavior. This study is the first to compare the effectiveness and performance of different green human resource management practices using data from the Chinese electric vehicle industry, providing insights for industrial environmental management and contributing to the growing body of literature. •Effects of different green human resource management (GHRM) practices are compared.•A model based on AMO, SET and SVF theories was verified in electric vehicle sector.•Structural equation modeling and IPMA were performed.•Green reward management negatively influences employee green behavior (EGB).•POGS mediates/EGV moderates certain GHRM practices - EGB relationships, not all.